2006
DOI: 10.1111/j.1460-9568.2006.04967.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of spike timing to the information transmitted by HVC neurons

Abstract: In many species, neurons with highly selective stimulus-response properties characterize higher order sensory areas and/or sensory motor areas of the CNS. In the songbird nuclei, the responses of HVC (used as a proper name) neurons during playback of the bird's own song (BOS) are probably one of the most striking examples of selectivity for natural stimuli. We examined here to what extent spike-timing carries information about natural and time-reversed versions of the BOS. From a heterogenous population of 107… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…This is because I * (S P , S; τ ) can have piecewise constant intervals (e. g. Victor and Purpura, 1996;Di Lorenzo and Victor, 2003;Roussin et al, 2008;Huetz et al, 2006Huetz et al, , 2009. Different criteria have been chosen in experimental studies that apply the discrimination analysis, but often there is not an explicit explanation of how to calculate τ * .…”
Section: I(r S) = R S P(r S) Log P(r S) P(r)p(s) mentioning
confidence: 99%
See 2 more Smart Citations
“…This is because I * (S P , S; τ ) can have piecewise constant intervals (e. g. Victor and Purpura, 1996;Di Lorenzo and Victor, 2003;Roussin et al, 2008;Huetz et al, 2006Huetz et al, , 2009. Different criteria have been chosen in experimental studies that apply the discrimination analysis, but often there is not an explicit explanation of how to calculate τ * .…”
Section: I(r S) = R S P(r S) Log P(r S) P(r)p(s) mentioning
confidence: 99%
“…Different criteria have been chosen in experimental studies that apply the discrimination analysis, but often there is not an explicit explanation of how to calculate τ * . In Huetz et al (2006) and Wohlgemuth and Ronacher (2007), the average of τ is taken when a plateau is obtained. In Roussin et al (2008) they comment that the influence of temporal coding may be underestimated because they consider as rate coding any case in which I * max (S P , S) is obtained for τ = ∞, even if lower time scales provide the same information.…”
Section: I(r S) = R S P(r S) Log P(r S) P(r)p(s) mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous auditory studies ( Chase and Young 2006;Huetz et al 2006), the temporal resolution that yields the maximum mutual information has been identified as the time scale most likely used by a certain auditory stage when processing temporal information. The present study showed that the best temporal resolution, determined by q, can be biased toward low values by variations in average rate.…”
Section: Best Temporal Resolutionmentioning
confidence: 99%
“…The mutual information quantified by the spike-distance metric indicates the efficiency of spike timing in coding the stimuli at different temporal resolutions. Although Victor and Purpura (1997) state that this approach may not incorporate all types of temporal information as an optimal temporal measure, this approach has been used in recent auditory studies as a general evaluation of the contribution of temporal information compared to that of average rate (Chase and Young 2006;Edeline 2004/2005;Huetz et al 2006). In the present study, the spike-distance metric was compared to other temporal measures for tone-innoise responses.…”
Section: Introductionmentioning
confidence: 99%